2009
DOI: 10.1021/ja902800f
|View full text |Cite
|
Sign up to set email alerts
|

Optical Activity and Chiral Memory of Thiol-Capped CdTe Nanocrystals

Abstract: CdTe nanocrystals (NCs) passivated with chiral ligands d- and l-cysteinemethylester hydrochloride were prepared and observed to exhibit characteristic CD profiles with symmetrical mirror images depending on the chirality of the capping ligand. The optical activity of CdTe NCs is shown to originate from the distorted CdS shell including chiral capping molecules. The chirality of the NC surface is maintained even after ligand exchange with an achiral thiol, providing an unprecedented chiral memory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
206
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(223 citation statements)
references
References 30 publications
3
206
2
7
Order By: Relevance
“…10 More recent reports on chiral CdTe based nanoparticles have also been published. 11,12 There is also a very recent theoretical work, which demonstrated that the electric field of the metal or semiconductor nanoparticle enhances the signal from the chiral stabiliser and other chiral species.13 Chirality is a common occurrence in the natural world and chiral compounds have very important applications in chemistry, biology, pharmacology and medicine. Therefore chiral nanoparticles have been envisaged to play an important role in science and technology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 More recent reports on chiral CdTe based nanoparticles have also been published. 11,12 There is also a very recent theoretical work, which demonstrated that the electric field of the metal or semiconductor nanoparticle enhances the signal from the chiral stabiliser and other chiral species.13 Chirality is a common occurrence in the natural world and chiral compounds have very important applications in chemistry, biology, pharmacology and medicine. Therefore chiral nanoparticles have been envisaged to play an important role in science and technology.…”
mentioning
confidence: 99%
“…10 More recent reports on chiral CdTe based nanoparticles have also been published. 11,12 There is also a very recent theoretical work, which demonstrated that the electric field of the metal or semiconductor nanoparticle enhances the signal from the chiral stabiliser and other chiral species.…”
mentioning
confidence: 99%
“…The red shift of previous silicon with styrene might be due to specific interaction between silicon surface and aromatic ring of the styrene units [21]. We have reported that the emission quantum yield of silicon nanoparticles with styrene molecules (emission wavelength = 680 nm) was found to be 55 %.…”
Section: Emission Properties Of Silicon Nanoparticles With Chiral Molmentioning
confidence: 94%
“…In particular, lanthanide complexes with chiral molecules show large CPL signals, which are expected to be useful in future chiroptical applications such as three dimensional display and chiroptical memory [20]. Chiroptical memory and sensor using CdTe, and CdSe/ZnO nanoparticles rapped with chiral molecules have been suggested [21][22]. Recently, induced CD and CPL properties in CdSe quantum dots have been reported [23].…”
Section: Introductionmentioning
confidence: 99%
“…The NPs prepared via the hot-soap method were firstly dispersed in chloroform, which were subjected to the ligand-exchange with TCB by a simultaneous phase transfer method to give aqueous dispersions. 21 1-Butylimidazolium Tf 2 N (bmimTf 2 N) was chosen as a representative IL. All NPs were dispersed in bmimTf 2 N by a simple liquidliquid extraction technique from aqueous dispersions of equivolume.…”
mentioning
confidence: 99%